The welcoming - Roberts, Nora (Severn House, 2019)
"Visitors come to Charity's friendly little inn to escape their ordinary lives. But FBI Agent Roman DeWinter knows something ugly is going on beneath the cozy surface. His mission is to expose the dangerous criminal gang operating out of the inn. Going undercover, Roman begins his investigation - which puts Charity's life on the line. A hit-and-run attack leaves her shaken and bruised, but only Roman knows how close she came to death. And with the gang under pressure and about to be exposed, they're both in terrible danger ..."--Inside cover jacket